2017
DOI: 10.1111/liv.13291
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus long‐term impact of antiviral therapy nucleot(s)ide analogues (NUCs)

Abstract: The goal of antiviral therapy is to improve the quality of life and survival of patients with chronic hepatitis B (CHB) by halting the progression to cirrhosis, end‐stage liver disease or hepatocellular carcinoma (HCC), thus preventing anticipated liver‐related death. Oral administration of potent and less resistance‐prone nucleot(s)ide analogues (NUCs), such as entecavir (ETV) and tenofovir disoproxil fumarate (TDF) has become the most popular treatment strategy worldwide because of their excellent efficacy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
69
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 54 publications
0
69
0
Order By: Relevance
“…All guidelines of major liver associations have considered hepatitis B surface antigen (HBsAg) seroclearance as a functional cure of HBV infection and the ideal endpoint of HBV treatment . Unfortunately, clinical studies have shown that HBsAg seroclearance during long‐term Nuc therapy is a rare event . A large study involving 5,409 patients with hepatitis B e antigen (HBeAg)–negative chronic hepatitis B (CHB) even showed an annual incidence as low as 0.33% during 6‐year Nuc therapy .…”
mentioning
confidence: 99%
“…All guidelines of major liver associations have considered hepatitis B surface antigen (HBsAg) seroclearance as a functional cure of HBV infection and the ideal endpoint of HBV treatment . Unfortunately, clinical studies have shown that HBsAg seroclearance during long‐term Nuc therapy is a rare event . A large study involving 5,409 patients with hepatitis B e antigen (HBeAg)–negative chronic hepatitis B (CHB) even showed an annual incidence as low as 0.33% during 6‐year Nuc therapy .…”
mentioning
confidence: 99%
“…However, the risk of occurrence of HCC in patients remains in those with initially extensive fibrosis or cirrhosis (F3 and F4 stages), even if it is significantly reduced in patients treated with NUCs . The main limitations of NUCs therapy is that it is indefinite and associated with a slow decline and a low rate of HBsAg loss . Although stopping NUCs is a viable option in patients with confirmed HBsAg loss, it is often associated with reactivation .…”
Section: Hbv and Hdvmentioning
confidence: 99%
“…Definitely, the future objective of HBV therapy is to have a finite treatment inducing a high rate of HBsAg loss with, if possible, disappearance of cccDNA. The future of HBV therapy will include a combination of more potent immunomodulators and antivirals with different targets (viral entry, protein synthesis, protein‐protein interaction) with strategies that will restore innate and adaptive immune response, completely block HBV replication and eradicate or silence HBV cccDNA . Obviously, to reduce the global health burden of HBV infection, in addition to treatment of chronic carriers, vaccination will need to be scaled‐up to reduce vertical transmission and the number of new cases …”
Section: Hbv and Hdvmentioning
confidence: 99%
“…Nucleos(t)ide analogues are predominantly eliminated via the renal route by a combination of glomerular filtration followed by active tubular secretion. Long‐term therapy with NA, in particular with nucleotide analogues, may lead to proximal renal tubular dysfunction followed by glomerular damage in some patients . Putative mechanisms of proximal tubular damage, such as alterations in renal tubular transporters, apoptosis, and mitochondrial toxicity (NA inhibits mitochondrial polymerase) in proximal tubules, have been identified .…”
Section: Introductionmentioning
confidence: 99%